COGNITIVE EFFORT AS A COMPONENT OF TRANSLATOR’S STRATEGY - ГРИЦІВ, Наталія; МЕЛЬНИЧУК, Оксана (Київський національний університет імені Тараса Шевченка, 2022)
The article examines the translator's cognitive strategy from the perspective of its key component , i.e. cognitive effort. The relevance of the discussed issue is determined by the fact that translation activity from a cognitive perspective attracts the attention of many scholars, and the heyday of this activity falls on the border of the 20–21 centuries. Meaning-making as a fundamental aspect of cognitive effort is to be analyzed. The study of mental processes in translation is of high relevance today. A noticeable shift towards the priority of understanding the cognitive process, as well as accumulation of information and knowledge that translator acquires through training and experience has become noticeable. In the research the following methods were used: the method of theoretical data collection and the method of analysis and evaluation of the obtained data. We consider metacognition to be the basis of a translator's cognitive strategy and understand it as strategic control over complex cognitive tasks, in particular translation. Close attention is paid to metacognition as a conscious control over the translator's cognitive tasks. Cognitive effort is considered as a combination of cognitive load with cognitive abilities that should be applied to solve a translation task. The article examines text-centric and translation-centric manifestations of cognitive effort. In addition, it is necessary to consider the subject field of the translator's cognitive resource, to analyze the designation of the cognitive resource at work in the process of translation. In order to illustrate the possibilities of translation, we rely on V. Lerscher's basic, extended and complex structures. On the one hand, the article revealed that simpler structures are rendered in literal translation and require less cognitive effort. On the other hand, more complex structures require considerable cognitive effort. The obtained results are the basis for further study of the cognitive resource as the main leverage in the activity of the translator.

У статті розглядається когнітивна стратегія перекладача з позиції її ключового компонента – когнітивного зусилля. Актуальність обговорюваного питання зумовлена тим, що перекладацька діяльність із когнітивного ракурсу привертає увагу багатьох науковців, а її розквіт припадає на межу ХХ–ХХІ ст. Смислотворення як фундаментальний аспект когнітивного зусилля потребує наукового аналізу. Вивчення розумових процесів (mental processes) у перекладі є дуже актуальним і малодослідженим. Останнім часом помітним є зсув у бік пріоритетності розуміння когнітивного процесу та накопичення інформації і знань, які перекладач отримує шляхом навчання й набуття досвіду. У процесі дослідження були використані метод збору теоретичних даних і метод аналізу й оцінки отриманих даних. Метапізнання вважаємо основою когнітивної стратегії перекладача та розуміємо як стратегічний контроль над складними когнітивними завданнями, зокрема перекладом. Пильну увагу приділено метакогніції як свідомому та керованому контролю над когнітивними завданнями перекладача. Когнітивне зусилля визначається як поєднання когнітивного навантаження з когнітивними здібностями, які необхідно застосовувати для вирішення перекладацького завдання. У статті розглядаються текстоцентричний та перекладацько-центричний вияви когнітивного зусилля, зокрема пропонується аналіз предметного поля когнітивного ресурсу перекладача, проаналізувати позначення когнітивного ресурсу на роботі у процесі перекладу. З метою ілюстрації можливостей перекладу спираємося на базову, розширену та складну структури В. Лершера. Вдалося констатувати, що простіші структури відображаються в буквальному перекладі та потребують докладання менших когнітивних зусиль, на відміну від більш складних структур. Отримані результати можуть використовуватись для подальшого вивчення когнітивного ресурсу як головного складника в діяльності перекладача.
КОГНІТИВНЕ ЗУСИЛЛЯ ЯК КОМПОНЕНТ СТРАТЕГІЇ ПЕРЕКЛАДАЧА
Keywords: переклад; когнітивне перекладознавство; перекладацька стратегія; когнітивне зусилля; метапізнання; translation; cognitive translation studies; translation strategy; cognitive effort; metacognition